A Study on the Level of Ethics at a Malaysian Private Higher Learning Institution: Comparison between Foundation and Undergraduate Technical-based Students - Khalid Ali, Khalidah; Salleh, Rohani; Sabdin, Mashitah (International Journal of Basic & Applied Sciences IJBAS- IJENS, 2010)
The environment and socialization process to which students are exposed remain as important factors contributing to academic success and character building. The Malaysian educational system, at both primary and tertiary levels have consistently emphasized on the importance of nurturing moral values and ethics among students. However, ethical problems among the Generation Y are often highlighted, be it at home or the workplace. As the general well being and prosperity of a nation depend largely on the internalization of good moral values among members of the community, an exploratory study was initiated to compare the level of ethics possessed by foundation and final year Engineering and Technology students at a higher learning institution in Malaysia. This paper aims to report on the research findings. A questionnaire was developed to measure five universally accepted moral values: Integrity, Honesty, Respect for humans and non-humans, Self Control and Courage. The comparative results of the study will give an indication whether the environment of the University has significantly contributed in shaping the ethical values of the students prior to joining the labour market. The findings may also show the extent of the contribution and effectiveness of ethics related subjects in developing the moral values of students.